2011
DOI: 10.1103/physrevb.84.214423
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical effect on the non-Abelian spin-orbital gauge field of a curved surface

Abstract: The geometrical effect of a two-dimensional electron gas system with the Rashba and Dresselhaus spin-orbital interactions on a curved surface is studied; it corresponds to a non-Abelian gauge field and a scalar field. The behavior of electrons with spin on a curved space can be transformed into that of a simple system of an electron with spin on a flat surface with a geometrical metric tensor. In addition to the dynamic phase of traveling electrons on a flat surface, a geometrical phase induced by curved space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This kind of curvature induced geometric potential can possibly induce local anisotropy or local effective magnetic field on curved surfaces. [ 5 ] Magnetism in curved geometries has been rather intensively discussed recently [ 70 ] and curvature induced local anisotropy and effective magnetic field can then counterbalance fluctuations and sustain spontaneous magnetization. Therefore magnetism in 2D curved system can also arise from the curvature induced anisotropy.…”
Section: Low Dimensional Theory For Magnetizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of curvature induced geometric potential can possibly induce local anisotropy or local effective magnetic field on curved surfaces. [ 5 ] Magnetism in curved geometries has been rather intensively discussed recently [ 70 ] and curvature induced local anisotropy and effective magnetic field can then counterbalance fluctuations and sustain spontaneous magnetization. Therefore magnetism in 2D curved system can also arise from the curvature induced anisotropy.…”
Section: Low Dimensional Theory For Magnetizationmentioning
confidence: 99%
“…Recently, intensive studies suggested that a curved 2D system introduces effective magnetic field, which can possibly counterbalance fluctuations. [ 5 ] Last, current results of magnetic space group and ab initio calculations of 2D vdW magnetic system are summarized in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of the spin-orbit interactions (SOI) on the momentum of the charge carriers suggests that the SOI can be manipulated by introducing (real-space) geometrical curvature into the (constrained) motion of charge carriers so that the direction and magnitude of their momentum vary with their positions [1]. The modification of the effective SOI and appearance of curvature-induced terms [2,3] due to the curved motion has led to various interesting phenomena, such the modification to the spin texture [4,5], spin precession [6,7], and charge density [8], suggesting potential applications for the generation of spin-polarized currents [9,10]. Recently, the independent geometrical control of the spin and charge resistances in a curved nanosystem has been demonstrated experimentally [11].…”
Section: Introductionmentioning
confidence: 99%
“…The first term on the right of the equal sign comprises the kinetic energy, the second term the SOI, and the third term the potential energy terms due to the applied potential, da Costa potential, and applied magnetization coupling. We obtain the eigenstates and eigenvectors of the Hamiltonian through direct numerical diagonalization of the real-space finite-difference approximation of the Hamiltonian equation (7), which would be described in detail in the following sub-sections.…”
mentioning
confidence: 99%
“…The dependence of the spin-orbit interactions (SOI) on the momentum of the charge carriers suggests that the SOI can be manipulated by introducing (real-space) geometrical curvature into the (constrained) motion of charge carriers so that the direction and magnitude of their momentum vary with their positions [1]. The modification of the effective SOI and appearance of curvature-induced terms [2,3] due to the curved motion has led to various interesting phenomena, such the modification to the spin texture [4,5], spin precession [6,7], and charge density [8], suggesting potential applications for the generation of spin-polarized currents [9,10]. Recently, the independent geometrical control of the spin and charge resistances in a curved nanosystem has been demonstrated experimentally [11].…”
Section: Introductionmentioning
confidence: 99%